EKSPLOITASI FAUNA DI SITUS LIANGAN, TEMANGGUNG: KAJIAN ARKEOZOOLOGI - Sofwan Noerwidi (Berkala Arkeologi, 2017)
Liangan is a settlement site of Old Mataram in periodic of VI-X AD. Various aspects of ancient Javanese culture has been recovered from Liangan site, but has never been examined the relationship between human and fauna in the past. The study aims to determine the pattern of faunal exploitation through archaeozoological approach, which use ecofact (faunal bones and teeth) that were found in the 2016 excavation campaign. This study conducts qualitative analysis of morphological character of the bones and teeth. Archaeozoological study is covering biological aspects of fauna, and cultural aspects related to human activity. These aspects are including anatomical preservation condition, taphonomy (deposition process), taxonomy (species), age estimation and faunal diet pattern. In the result, mainly bones and teeth are identified as buffalo (Bubalus sp). Taphonomical preservation condition of buffalo bone indicating faunal exploitation for human consumption. The climatic condition of Sindoro highland which is not buffalo’s natural habitat indicates an intensive human intervention as domestication. This study shows that buffalo on Liangan site eat more leaves as browser which probably supplied by human.